(untitled) (Biodiversitas Journal of Biological Diversity, 2017)
Bedjo. 2017. The potential of various isolates of Spodoptera litura Nuclear Polyhedrosis Viruses from East Java (Indonesia) to control Spodoptera litura on soybean. Biodiversitas 18: 582-588. The study on potential of six isolates of SlNPV which are originally from East Java to control S. litura on soybean was conducted at the Entomology Laboratory, Plant Protection Department of Indonesian Legumes and Tuber Crops Research Institute during May to August 2015. The experiments were conducted to evaluate the potential of six isolates of SlNPV, namely: SINPV JTM 02-1, SINPV JTM 02-2, SINPV JTM 02-3, SINPV JTM 02-4. SINPV JTM 02-5 and SINPV JTM 97c (as control, a virulent strain uses five virus concentrations (1x10Â°, 1x106, 1x108, 1x1010, and 1x1012 PIBs/mL) to control the existence of S. litura instar-3. The data of the time for larvae to stop eating and their mortality were analyzed using MSTATC computer software and Hsinchi Probit program was used to analyze the 50% lethal concentration (LC50) and 50% lethal time (LT50). The study showed that the larvaeâ€™s will to stopeating, their mortality, LC50, and LT50 were significantly influenced by the interaction between SINPV isolate and the inoculated virus concentration. These potential parameters were also different among the larvae instar of tested S. litura. The potential of each isolates was higher at instar-3 than the other. Besides that, SINPV JTM 97c, SINPV JTM 02-5 showed the highest potential to control S. litura. It can be seen from instar-3, LC50 that is effective to kill 50% of the larvae population of SlNPV JTM 02-5 was between 1x1010 - 1x1012 PIBs/mL with LT50 between 170-207 Hours After Inoculation (HAI). It is revealed that SINPV JTM 02-5 has more potential as biopesticide to control S. litura than the other tested isolates.